Triassic-Jurassic development and evolution of the Atuel depocentre, Neuquén basin, Mendoza province - Giambiagi, L. (2008)
The Atuel depocentre corresponds to a Late Triassic - Early Jurassic NNW-trending subbasin, located in the northern sector of the Neuquén basin. Based on pre-existing stratigraphical data and present structural analysis we propose that the Atuel depocentre is bounded by the presence of two NNW-trending major normal faults, named Alumbre and La Manga. These faults are inferred to have controlled the development of two west-facing half-grabens: the Río Blanco, a completely emerged half-graben, and the western Arroyo Malo, a completely submerged half-graben. The structural model presented here is based on the assumption that both, the basement structural grain and the regional extension direction, exerted a first-order control in the development and evolution of the Atuel depocentre. During the early stage of rifting (pre-Rhaetian - Middle Hettangian) the pre-Triassic Alumbre and La Manga faults reactivated in an oblique mode. During the second episode of rifting, both Alumbre and La Manga faults continued to play, while WNW-trending normal fault developed in order to accommodate the strain inside both half-grabens. The third extensional event began with an abrupt marine rise inside the Arroyo Malo half-graben during late Middle Hettangian, as a result of the last displacement of the Alumbre fault, and finished with an abrupt marine drop associated with the desactivation of the La Manga fault.